PENGARUH LINGKUNGAN FISIK, KUALITAS LAYANAN, DAN KUALITAS PRODUK TERHADAP KEPUASAN KONSUMEN PADA KAFE SEMILIR BOJONEGORO - Edy Suhartono (ITB AAS Indonesia Surakarta, 2024)
Abstract The location of this research is Semilir Cafe on JL. First Lieutenant Suyitno, Bojonegoro Regency. The reason Semilir Cafe was chosen as the research location was because Semilir Cafe has a unique dining concept, namely a garden atmosphere on the edge of Bengawan Solo. The object of this research is related to